Taxonomic revision of the Pheidole megacephala species-group (Hymenoptera, Formicidae) from the Malagasy Region - Salata,Sebastian; Fisher,Brian L. (PeerJ, 2022)
Background The Malagasy Region, one of the top megadiversity regions, hosts one of the highest numbers of endemic and threatened organisms on earth. One of the most spectacular examples of ant radiation on the island has occurred in the hyperdiverse genus Pheidole. To this date, there are 135 described Madagascan Pheidole divided into 16 species-groups, and 97% of Malagasy species are endemic to the island. This study is a taxonomic revision of the Pheidole megacephala group, one of only two species-groups comprising a combination of native, endemic taxa and widely distributed introduced species. Methods The diversity of the Malagasy members of the megacephala group was assessed via application of qualitative morphological and DNA sequence data. Qualitative, external morphological characteristics (e.g., head shape, gaster sculpture, body colouration) were evaluated in order to create a priori grouping hypotheses, and confirm and improve species delimitation. Mitochondrial DNA sequences from cytochrome oxidase I (COI) gene fragments were analyzed to test the putative species previously delimited by morphological analyses. Results We recognize three species belonging to the megacephala group: P. megacephala (Fabricius, 1793), P. megatron Fischer & Fisher, 2013 and P. spinosa Forel, 1891 stat. nov. Pheidole spinosa is redescribed and elevated to the species level. The following names are recognized as junior synonyms of P. spinosa: P. megacephala scabrior Forel, 1891 syn. nov., P. picata Forel, 1891 syn. nov., P. picata gietleni Forel, 1905 syn. nov., P. picata bernhardae Emery, 1915 syn. nov., and P. decepticon Fischer & Fisher, 2013 syn. nov. The results are supplemented with an identification key to species for major workers of the megacephala group, high-resolution images for major and minor workers, and comments on the distribution and biology of all Malagasy members of the group. Our study revealed that Pheidole megacephala, a species listed among the 100 worst invasive species worldwide, occurs in both natural and disturbed sites in the Malagasy region. The two remaining members of the megacephala group, most likely endemic to this region, are also present in anthropogenic habitats and often co-occur with P. megacephala. It appears that the Malagasy members of the group are generalists and dominant in anthropogenic habitats. Additionally, we documented the presence of supermajors in colonies of P. spinosa—a phenomenon previously not known for this group.
Keywords: Biodiversity; Entomology; Taxonomy; Biogeography; Phylogeny; Invasive species; Madagascar